The Effect of Fiscal Service Quality on Taxpayer Compliance With Taxpayer Awareness as an Intervening Variable - Yohana Yustika Sari; M. Yudy Rachman (Enrichment : Journal of Management, 2022)
This study aims to analyze the effect of the intervening variable on taxpayer awareness on the relationship between the quality of tax services and taxpayer compliance. The population of this research is individual taxpayers registered at the Tax Service Office (KPP) Pratama Banjarbaru, while the research sample is 100 individual taxpayers of certain entrepreneurs. Data was collected by using questionnaires, data analysis and hypothesis testing using path analysis. The results of the study show that the quality of tax service services directly affect taxpayer compliance, and the quality of tax service services is also proven to have an indirect effect on taxpayer compliance through taxpayer awareness as an intervening variable. This means that the better the quality of service, the taxpayer compliance will also increase. Service quality also has an indirect effect on taxpayer compliance through taxpayer awareness. With good service quality, taxpayer awareness will also increase and will also increase taxpayer compliance.